Foreign experience of anti-crisis management of medical institutions - Shchyrina, Katherine; Koshova, Svitlana; Parkhomenko-Kutsevil, Oksana (ScienceRise: Medical Science, 2022)
The main components of the crisis management system of medical institutions were highlighted. Crisis situations will be understood as the inability of medical institutions to provide the population with medical services on time due to lack of various resources. As a result of catastrophes, natural disasters, armed conflicts, crisis situations arise when medical institutions are not able to fully provide the population with medical services, there is a lack of funding, human and material resources. Ukraine is no exception, as the armed conflict in the East in 2014 and Russia’s full-scale invasion of Ukraine confirmed the lack of sufficient labor, logistical resources and financial support to provide quality medical care to the population. In such conditions, there is a need to develop tools, means of overcoming crisis situations in healthcare facilities. The aim of the article is to systematize the recommendations for Ukraine on the formation of a system of crisis management of healthcare facilities. Materials and methods of the research. The basis for the study were provided by private clinics for analysis documents of financial and economic reporting for the pre- and post-crisis periods, as well as scientific works of famous Ukrainian and foreign scientists. The research used methods of analysis, comparison, medical and statistical method and system. The result of the study was an analysis of the state of funding for healthcare facilities in Ukraine and a comparative analysis with the state of funding for such facilities in other developed countries such as Italy, Germany, Sweden, France. Conclusions. The main components of the system of anti-crisis management of medical institutions in crisis conditions are: effective leadership, which is provided by managers and management staff; human resources; equal access to basic medicines, vaccines and technologies of guaranteed quality, safety, efficiency; a functioning health information system has been established; financing of healthcare institutions and their financial protection in case of crisis; the process of providing quality, safe and efficient medical services with minimal expenditure of resources. In most European countries, the basic functions of healthcare management (prioritization, financing, service delivery, supply planning, quality control) are decentralized and carried out at the level of regional or local authorities, or regional health insurance funds or trusts